Active flow and combustion control 2018 : papers contributed to the conference "Active Flow and Combustion Control 2018", September 19-21, 2018, Berlin, Germany /: papers contributed to the conference "Active Flow and Combustion Control 2018", September 19-21, 2018, Berlin, Germany. ([2019]) - Unknown
No abstract available